Synthesizing and Extending Resource Dependence Theory - Drees, Johannes M.; Heugens, Pursey P. M. A. R. (Journal of Management, 2013)
Resource dependence theory (RDT) has long been a premier framework for understanding organization-environmental relations, but an empirical synthesis of its predictions is still lacking. Using meta-analysis, we consolidate 157 tests of RDT and corroborate its main predictions: organizations respond to resource dependencies by forming interorganizational arrangements like interlocks, alliances, joint ventures, in-sourcing arrangements, and mergers and acquisitions. In turn, these arrangements make them more autonomous and more legitimate. We also extend RDT in three ways. First, we “unpack” the theory by showing that the mechanisms linking arrangement formation to organizational autonomy and legitimacy differ across arrangements. Second, we address the question whether RDT is also a theory of organizational performance. We find that whereas autonomy positively mediates the relationship between arrangement formation and performance, legitimacy does not. This suggests that RDT can also explain organizational actions that have societal acceptance rather than economic performance as an ulterior motive. Third, we assess whether competition law is a boundary condition to RDT’s prescriptions. Specifically, we show that the adoption of the Horizontal Merger Guidelines in the U.S. has caused organizations to “flee” from mergers to less regulated arrangements like alliances and joint ventures, and has hurt the profitability of the remaining mergers.